2002
DOI: 10.1046/j.0141-9838.2001.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired immunoglobulin (Ig)G subclass antibodies to crude asexual Plasmodium falciparum lysates: evidence for association with protection for IgG1 and disease for IgG2

Abstract: There is longstanding evidence for a role of immunoglobulin (Ig)G in protection against malarial disease and infection. IgG1 and IgG3 have been shown to be particularly efficient at associating with monocytes in potentially protective mechanisms (i.e. antibody-dependent cellular inhibition, opsonization and phagocytosis). Conversely, there is some evidence that IgG2 (and possibly IgG4) antibodies may be antagonistic to this protection. The protective effect of IgG subclass antibody activity present before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
66
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 24 publications
12
66
1
Order By: Relevance
“…Another aspect of particular note concerns the detection of the anti-VSA antibodies of all four IgG isotypes, in the case of some isolates at very similar levels, which is consistent with an earlier report (23). The antibody response to crude parasite antigen preparations commonly comprises a mixture of all four IgG isotypes, but the response to defined P. falciparum asexual-stage antigens is usually more restricted and is dominated by cytophilic isotypes (4,18,41,57). In the profile that we observed here, IgG3 antibodies did predominate, although they were equivalent to IgG4 in children in terms of magnitude and equivalent to IgG2 in adults in terms of the IRR.…”
Section: Discussionsupporting
confidence: 69%
“…Another aspect of particular note concerns the detection of the anti-VSA antibodies of all four IgG isotypes, in the case of some isolates at very similar levels, which is consistent with an earlier report (23). The antibody response to crude parasite antigen preparations commonly comprises a mixture of all four IgG isotypes, but the response to defined P. falciparum asexual-stage antigens is usually more restricted and is dominated by cytophilic isotypes (4,18,41,57). In the profile that we observed here, IgG3 antibodies did predominate, although they were equivalent to IgG4 in children in terms of magnitude and equivalent to IgG2 in adults in terms of the IRR.…”
Section: Discussionsupporting
confidence: 69%
“…Most importantly, both adjuvants led to generation of cytophilic antibodies (mainly IgG1) (i.e., isotypes capable of supporting in vitro and in vivo antibody-dependent, monocyte-mediated parasite growth inhibition). Indeed, IgG1 and IgG3 anti-plasmodium antibodies, but not IgG2, IgG4, and IgM anti-plasmodium antibodies (1,32) or anti-MSP3 antibodies (40), have been associated with protection in humans, as well as in primates, and to be the key players of ADCI (6,8,15,(33)(34)(35). We also showed that these antibodies were also able to bind a nonsynthetic recombinant MSP3 molecule (rMSP3 210-380).…”
Section: Vol 73 2005mentioning
confidence: 74%
“…However, the Montanide formulation led to the withdrawal of an unacceptably high number of volunteers with severe local reactions, whereas the aluminum hydroxide formulation was generally well tolerated. The largely cytophilic IgG1 anti-MSP-3-specific profile of the humoral response may confer to the vaccine potential monocyte-mediated protective activity (1,32,40). This should be addressed in endemic area trials or with individuals exposed to malaria challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with humans have found a correlation between IgG1 and IgG3 levels and protection against severe disease (7,18,35); these two antibody isotypes have also been shown to be capable of mediating opsonization (20). Furthermore, passive transfer of malariaspecific IgG has been shown to reduce parasitemia in humans (8,11,40).…”
Section: Discussionmentioning
confidence: 99%